The relevance of the Pedagogical Coordinator in the School Environment: challenges and communication in teaching practices (Research, Society and Development, 2022)
This study presents the result of a research linked to the Research Line 1 (RL1) nominated Policies and Management of Primary and Superior Education of Specialization in Educational Management, a Post-Graduation Studies Program in Public Policies and Educational Management from Federal University of Santa Maria (UFSM) . The main goal of this research was to comprehend the relevant aspects which highlight the importance of the pedagogical coordinator’s practice related to teachers’ formation and practice in the Initiating Years of Primary School (AIEF) , and the main objectives are: to map the ambience in which the pedagogical coordinator performs; to give voice to the pedagogical coordinator for them to share their formation and personal/professional trajectory; to comprehend the formation processes on the school ambience from the narrative of the pedagogical coordinator; to describe the strategies adopted by the pedagogical coordinator while promoting the continuing formation of teachers; to verify the possible interventions of the pedagogical coordinator on the pedagogical practices developed by the teachers. The relevance of this research is justified by the performance of the pedagogical coordination regarding teachers’ continuing formation in primary school through the acts of their teaching formative trajectory. For that matter, through narrative by this research’s collaborator, it was observed that they remembered their practices as a teacher and as a pedagogical coordinator, as well as their formation processes. The methodology is based on narrative research to enhance the study of which feelings connect to the teaching practice. The information analysis was backed up by the narrative interview organized from guiding topics. The referential was built upon the studies of Abrahão, Bauer; Gaskell, Isaia & Bolzan, Libâneo, Marquezan, Nóvoa, Vasconcelos, amongst others. From the results of the dialogues along the researching and information analysis, the following topic-guides emerged: pedagogical practices at teaching formation, pedagogical practices on the pedagogical coordination and continuing formation at school. As a result, it was possible to acknowledge the experiences of the collaborator, as well as the overcoming and formation that happen in the school environment, as well as possible frustrations related to the establishment of formative processes due to the resistance of some teachers and the amount of time demanded for this practices.